Harnessing the sweet potential: the revival of honey dressing in modern wound care - Emanuele Primavera; Camilla Marzolani (Firenze University Press, 2023)
Honey dressings have found wide application in the past and are currently experiencing a resurgence due to their beneficial properties, which aid professionals in their daily practices. Manuka honey possesses properties that are suitable for debridement of chronic wounds, stoma-therapy, and burns. This cultural article aims to review the major literature and benefits of medical honey dressing and underline five important implications (i.e., alternative care for individuals experiencing antibiotic resistance, ease of application, faster healing, shorter hospital stays, and economic convenience in countries characterized by high financial constraints) that at this stage are underdeveloped in the literature.